2020
DOI: 10.5194/acp-2019-1218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temperature Effects on Optical Properties and Chemical Composition of Secondary Organic Aerosol Derived from <i>n</i>-Dodecane

Abstract: Abstract. Environmental temperature plays a vital role in controlling chemical transformations that lead to the formation of secondary organic aerosol (SOA), and ultimately impact composition and optical properties of the aerosol particles. In this study, we investigate optical properties of n-dodecane secondary organic aerosol under two temperature conditions: 5 °C and 25 °C. It is shown that low temperature can enhance the real part of refractive index (RI) of the SOA at the wavelengths of 532 nm and 375 nm.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…For the same precursor, under similar VOC / NO x conditions, the lower the temperature, the higher the mass of particulate matter. Lower temperatures can affect the partitioning process of organic vapour and facilitate the formation of particles, which in turn increases the particle mass concentration in the reaction system, and this is consistent with previous experimental reports (Ding et al, 2017;Li et al, 2020;Sheehan and Bowman, 2001;Takekawa et al, 2003;Warren et al, 2009). Meanwhile, with the increase in the VOC/NO x ratio value, the particle mass concentration increases (S. .…”
Section: Effect Of No X and So 2 On Particle Formationsupporting
confidence: 91%
See 2 more Smart Citations
“…For the same precursor, under similar VOC / NO x conditions, the lower the temperature, the higher the mass of particulate matter. Lower temperatures can affect the partitioning process of organic vapour and facilitate the formation of particles, which in turn increases the particle mass concentration in the reaction system, and this is consistent with previous experimental reports (Ding et al, 2017;Li et al, 2020;Sheehan and Bowman, 2001;Takekawa et al, 2003;Warren et al, 2009). Meanwhile, with the increase in the VOC/NO x ratio value, the particle mass concentration increases (S. .…”
Section: Effect Of No X and So 2 On Particle Formationsupporting
confidence: 91%
“…Studies of single long-chain alkanes (e.g. n-decane, n-undecane, n-dodecane, n-tridecane, 2,6,10trimethyl dodecane, nonyl-cyclohexane) include reaction kinetics (Lamkaddam et al, 2019;Shi et al, 2019a, b), reaction mechanisms (Li et al, 2020(Li et al, , 2021a, analysis of gas phase and particle phase products (Fahnestock et al, 2015;Lamkaddam et al, 2020), quantification of particle yield (Docherty et al, 2021;Loza et al, 2014), and particle physicochemical properties (J. Li et al, 2020Li et al, , 2021a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of photochemical simulation experiments of hydrocarbons and NOx were designed and conducted according to the atmospheric conditions in Lanzhou and Beijing (Zhang and Li, 1998). Then a serious environmental issues were studied based on the smog chambers constructed with various size in the past decades, including the mechanism of photochemical reaction (Liu et al, 2017;Wang et al, 2014;Wu et al, 2007), ozone and SOA formation (Li et al, 2018a;Ma et al, 2018;Wang et al, 2015), biomass burning reactions (Zhang et al, 2011), the photochemical process of the gasoline and diesel (Chen et al, 2019a;Chen et al, 2019b;Kamens et al, 2011), physicochemical properties of SOA formed under various conditions (Li et al, 2017a;Li et al, 2020;Li et al, 2018b;Peng et al, 2018;Zhang et al, 2020), et al However, most of the chambers constructed in China were indoor smog chambers, establishment large-scale outdoor smog chambers in China was limited. In order to study the atmospheric pollution process close to China's actual atmospheric environment, it was necessary to build a large outdoor smog chamber in China.…”
Section: Introductionmentioning
confidence: 99%
“…A scanning mobility particle sizer (SMPS 3080, TSI Inc., USA) was used to measure the size distribution of particles within the chamber. Previous studies that have measured the density of alkane SOA have found a range from 1 to 1.4 g cm −3 (Li et al, 2020(Li et al, , 2022Lim and Ziemann, 2009;Loza et al, 2014). Aerosols from each alkane experiment in this study were assumed to have a density of 1.2 g cm −3 .…”
Section: Methodsmentioning
confidence: 99%